English as a Medium of Instruction (EMI) in Indonesian elementary schools: Features, problems, possibilities, and prospects - German, Emilius; Pujiastuti, Ani; Estillomo, Ryan Besa (EduLite: Journal of English Education, Literature and Culture, 2025)
The implementation of English as a medium of instruction (EMI) in Indonesian primary schools has resulted in positive and negative effects. The objective of this study is to identify the characteristics, challenges, possibilities and prospects of EMI in Indonesian primary schools. A convergent parallel mixed approach was employed to obtain insight from 32 teachers working in EMI schools. The results show that the dual-medium strategy is the main approach assisting students in gradually transitioning from their mother language to English based on their various language proficiency and their parents’ favor.  However, many teachers find it difficult to explain difficult concepts in English, particularly to students who have limited competencies.  Although the majority of teachers believe that there are enough EMI teachers, there is a shortage of certified and experienced educators as well as limited opportunities for ongoing professional development. The prospects for EMI remain optimistic despite these challenges. Participants expect future expansion powered by enhanced institutional support, improved teacher training, optimized resource distribution, and increased stakeholder engagement. These elements are essential for the sustainable and effective implementation of EMI within Indonesia's diverse educational setting